2019
DOI: 10.1016/j.copbio.2019.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Improving anaerobic digestion via direct interspecies electron transfer requires development of suitable characterization methods

Abstract: Many recent AD studies mistakenly link performance improvements exclusively to DIET.• Unequivocally proving the occurrence of DIET requires a complex set of methods.• This paper groups DIET characterization methods in four categories and discusses their strengths and weaknesses. • This paper presents promising DIET detection approaches that merit further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(40 citation statements)
references
References 77 publications
0
40
0
Order By: Relevance
“…In BESs, EF with an applied or in-situ potential can use acetate, propionate, and butyrate present majorly in waste effluents for chain elongation to produce MCFAs. Various experiments have been carried out for producing n-caprylate using ethanol as an electron donor [123]. Clostridium kluyveri observed the formation of caproate (C6) and caprylate (C8) from acetate in a BES at −0.9V against a normal hydrogen electrode (NHE) on the cathode with hydrogen provided in-situ as an electron donor [121].…”
Section: Medium-chain Fatty Acids (Mcfa)mentioning
confidence: 99%
“…In BESs, EF with an applied or in-situ potential can use acetate, propionate, and butyrate present majorly in waste effluents for chain elongation to produce MCFAs. Various experiments have been carried out for producing n-caprylate using ethanol as an electron donor [123]. Clostridium kluyveri observed the formation of caproate (C6) and caprylate (C8) from acetate in a BES at −0.9V against a normal hydrogen electrode (NHE) on the cathode with hydrogen provided in-situ as an electron donor [121].…”
Section: Medium-chain Fatty Acids (Mcfa)mentioning
confidence: 99%
“…Our results reveal first that S. oneidensis MR-1 improved methane production. Indeed, although exoelectrogenic bacteria have been shown to favor DIET-mediated methane production [7,8,10], only Geobacter bacterial species have been found so far to participate in DIET with methanogens [19]. Shewanella species and methanogens have been previously detected simultaneously in the same niche [26,27], but no evidence was given for increasing methane production by exoelectrogenic activity.…”
Section: Increase Of Methane Production Performance With S Oneidensimentioning
confidence: 99%
“…Geobacter spp., with methanogenic archaea, but major electroactive microorganisms such as Geobacter spp. are not always detected in improved methane production systems [19]. Two recent studies suggested that conductive magnetite accelerates acetoclastic methanogenesis [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future researches should direct more effort for verifying DIET activation and/or other potential changes in anaerobic growth, which can be implicated in the observed enhancement in CH 4 production rate and/or yield. Recently, Van Steendam et al [132] evaluated some advanced DIET identification methods, including fluorescence in situ hybridization, cyclic voltammetry, scanning, transmission electron microscope, and various (meta-)omic approaches; the usage of combined methods for confirming DIET occurrence was finally recommended. Additionally, Neu et al [133] presented temperature-resolved THz spectroscopy that can easily measure the conductivity of wild-type pili.…”
Section: (B) Scientific Perspectivesmentioning
confidence: 99%